Resposta :
Resposta:
Olá!!!!
[tex]3(x - 6) = 9 \\ 3x - 18= 9 \\ 3x = 18 + 9 \\ 3x = 27 \\ x =27 \div 3 \\ x = 9[/tex]
Att:MIRANDA <3
![Ver imagem MIRANDASANTOSEMILLYV](https://pt-static.z-dn.net/files/d22/34d25c07c74d22b22f9bc0917dd2fda2.jpg)
Vamos l´:
3(x - 6) = 9
x - 6 = 9/3
x - 6 = 3
x = 3 + 6
x = 9
Espero ter ajudado !!!
Resposta:
Olá!!!!
[tex]3(x - 6) = 9 \\ 3x - 18= 9 \\ 3x = 18 + 9 \\ 3x = 27 \\ x =27 \div 3 \\ x = 9[/tex]
Vamos l´:
3(x - 6) = 9
x - 6 = 9/3
x - 6 = 3
x = 3 + 6
x = 9
Espero ter ajudado !!!